Case Report: Hyperinflammatory Status in an Immunocompromised Child With a Highly Sustained Viral Load of SARS-CoV-2 - Moragas, Matias; Gomez, Sandra; Fernández, María Florencia; Golemba, Marcelo Dario; Palladino, Marcela; Borgnia, Daniela; Ruvinsky, Silvina; Fraquelli, Lidia; Buchovsky, Ana; Bologna, Rosa; Mangano, Andrea (Frontiers in Medicine, 2021)
Coronavirus disease 2019 (COVID-19) is spreading throughout the world. Limited data are available for the dynamics of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) viral load (VL) in immunocompromised pediatric patients. Here, we report the clinical characteristics and the dynamics of SARS-CoV-2 VL of a pediatric patient with acute myeloid leukemia who developed a hyperinflammatory status mimicked MIS-C. The clinical course was characterized by the late onset of fever, GI symptoms, rash, and respiratory distress, including oxygen requirement with sustained VL of SARS-CoV-2 around 7 log10 RNA copies/mL for 6 weeks. It is important to note that the hyperinflammatory status developed early at the third week of hospitalization—in a context of high VL and immunocompromised status. All these characteristics make this clinical case unique. On the other hand, while many reports have characterized the dynamics of SARS-CoV-2 VL in adults and immunocompetent hosts, it remains unreported in pediatrics—even less in immunosuppressed children.